An empirical evaluation of students' perceptions of the nature of science : a comparison between groups - Edwards, Nazeem (School of Education, 2014)
In 1991 Evans and Schibeci used a modified Views of Science-Technology-Society (VOSTS) instrument to assess 434 Australian students' views on selected aspects of the Science-Technology-Society (STS) theme. In South Africa , Parker and Rochford (1995), and the writer Edwards et al. (1997) conducted and published further corroborative studies with more than 1400 students. Set in the context of the debate on the "traditional" and "contemporary" models of the nature of science (after Palmquist and Finley, 1997), this study measures, compares and interprets the response patterns of five convenient sample groups to 26 items on the modified VOSTS instrument. The three subscales measure students' perceptions of the definition of science, scientific method and how scientific knowledge changes. The reliability of the instrument was computed for Cape Town students using Cronbach's coefficient which yielded α = 0.78; and its content had been shown to be inherently valid at the time it was developed. A self-completion questionnaire was administered by the writer to four Cape Town student samples in 1995 during normal periods of instruction at two high schools, a technikon and a college of education. The samples comprised 320 year 10 high school science students, 340 year 12 high school science students, 108 electrical engineering students, and 55 first year college of education science students respectively. The 434 year 10 Australian students' (sample 5) responses were compared with the responses of their South African counterparts. In order to determine statistically significant differences between the response frequencies of the sample groups on the 26 items, the χ² - test statistic was used.